Belajar Bersama dan Menerapkan Manajemen Waktu Sejak Usia Dini - Tri Sulistyani; Diana Azwina; Rian Sri Rahayu; Muhammad Andrei Lesmono (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
Community service activities are aimed at knowing how to make children study hard (especially understanding English and Mathematics). Then to know how to apply time management well. Besides to find out how to help children to increase their daily needs in the Rempoa Domyadhu (Dompet Orphan and Dhu'afa) Orphanage. The method used in community service activities uses mentoring and discussion methods. The overall results obtained during the event included: materials, facilitators, training venues, and consumption. Received a very good response from all participants and were useful for service participants in completing school assignments and helping implement time management from an early age to adulthood later.